Destroying Stereotypes about the Innercity Poor - Per Jansen (The University of Alabama, 2022)
A student reflects on their participation in a research-focused community engagement project with the Day Labor Organizing Project (DLOP), a workers' center in Cincinnati, Ohio, that was attempting to organize day laborers and ensure the protection of their labor rights.